IMPROVING PRODUCTION OF SOFT-SHELLED SWIMMING CRABS: MACROSCOPIC SIGNS OF MOLTING AS A TOOL FOR SELECTION AND MANAGEMENT OF Callinectes danae AND Callinectes exasperatus (PORTUNIDAE, DECAPODA, CRUSTACEA) - Ostrensky, Antonio; Ventura, Robson; Corrêa, Angélica Maria Araújo; Santos, Gislaine Vieira; Castilho-Westphal, Gisela Geraldine (Archives of Veterinary Science, 2015)
In order to improve the efficiency of soft-shell crab production, we investigated whether it is technically viable to increase harvesting rates of soft-shelled crabs of the species Callinectes danae and C. exasperatus by selecting animals based on macroscopic molt signs and maintaining them in specific facilities. The study was conducted in three stages. In the first stage, macroscopic anatomic changes possibly related to the molting cycle identified under laboratory conditions. In the second stage we used the macroscopic clues observed in the first assay to select premolt animals harvested from their natural environments. Yet in this stage of the work, the relationship between the macroscopic changes and the microscopic signs of molting was evaluated. Lastly, an assay verified the technical feasibility of increasing the fraction of soft-shells in the total catch by selecting and maintaining premolt swimming crabs of species C. danae and C. exasperatus in specific facilities until the molt. Our results indicated that we can macroscopically identify, and therefore select, individuals in premolt phases II, III and IV that will soon molt, but further investigations are necessary to identify the requisite conditions for successful molting of individuals in premolt phase I.